If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8.2x + -4.9 = -66 Reorder the terms: -4.9 + 8.2x = -66 Solving -4.9 + 8.2x = -66 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4.9' to each side of the equation. -4.9 + 4.9 + 8.2x = -66 + 4.9 Combine like terms: -4.9 + 4.9 = 0.0 0.0 + 8.2x = -66 + 4.9 8.2x = -66 + 4.9 Combine like terms: -66 + 4.9 = -61.1 8.2x = -61.1 Divide each side by '8.2'. x = -7.451219512 Simplifying x = -7.451219512
| 7(-x-7x)=-595 | | 6x-2(x+3)=5x-1(x+2)x | | 5-3x=2x+1 | | 19a+4(x+1)=25 | | 10+j-3=6.5 | | 49x^3=9x | | x=50+0.75x | | 2-11x^2-8x+6x^2= | | -7+15+x=-2 | | 5.55=7t-8 | | -12t+50=-34 | | 10x-4y-5z= | | 2.04=x^12 | | 64t^2+16t-1=0 | | 10x+17-2=14x-8+4x | | 4w+3=2w+10 | | 10x+17-2=14a-8+4x | | -5x^2-41x+36=0 | | 3a+5(a-1)+7=2c | | -6h-5=31 | | 144=((6+x(2))+x)2 | | 3(8-4x)=-120 | | 2(9+3x)=-18 | | 2x+5=6x | | 7x-40+7x^2=0 | | X^4+3x^3-11x^2+99x+8=0 | | -4k+17= | | 16t^2+24t+9=0 | | f+9.42=37.68 | | 5(b+1)=4(b+3) | | 8a+48= | | n^2+n-182=0 |